Study of the short-range order of Co-W alloys electrodeposited using pulse current - Gerasimenko, D.V.; Tytarenko, V.V. (Physics and Chemistry of Solid State, 2023)
Pulsed electrodeposition modes allowed to obtain amorphous Co-W alloys. Using X-ray phase and spectral analysis methods, it was established that the deposition modes and the concentration of the amorphizing component (sodium tungstate salts) in an aqueous electrolyte solution affect the amorphization of alloys. The short-range atomic order was studied by X-ray diffraction analysis and the sizes of the regions of ordered arrangement of atoms were determined in X-ray amorphous Co-W alloys obtained by pulsed electrodeposition. The radial distribution function of atoms was analysed. The assumption is made that cobalt and tungsten atoms combine into configurations that are irregular polyhedrons.